The Effect of a Ketogenic Diet on Human Health and Diseases: A Literature Review - Kinga Bielas; Ewa Chodkowska; Kinga Dominiczak; Katarzyna Szafrańska; Aleksandra Mucha; Aleksander Szeps; Bartosz Zabrzeński; Jessika Schendzielorz (Quality in Sport)
Introduction and Aim. The ketogenic diet (KD), rich in fats and low in carbohydrates, induces a state of ketosis and metabolic changes. Used for over a century in epilepsy treatment, it is also gaining popularity in the therapy of other conditions, including metabolic, cardiovascular, oncological, and neurodegenerative diseases. The aim of this work is to review the literature concerning its effects, applications, and potential adverse effects.